2016
DOI: 10.1016/j.icarus.2015.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Surface ages of mid-size saturnian satellites

Abstract: The observations of the surfaces of the mid-sized Saturnian satellites made by Cassini-Huygens mission have shown a variety of features that allows study of the processes that took place and are taking place on those worlds. Research of the Saturnian satellite surfaces has clear implications not only for Saturn's history and Saturn's surroundings, but also for the Solar System. Crater counting from high definition images is very important and could serve for the determination of the age of the surfaces. In a r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 57 publications
(107 reference statements)
1
28
1
Order By: Relevance
“…Therefore, the dependence of cratering with time is the same as the dependence of encounters with time. Di Sisto & Zanardi (2016) found that this time dependence is well fitted by a logarithmic function given by:…”
Section: Satellite Agementioning
confidence: 95%
See 2 more Smart Citations
“…Therefore, the dependence of cratering with time is the same as the dependence of encounters with time. Di Sisto & Zanardi (2016) found that this time dependence is well fitted by a logarithmic function given by:…”
Section: Satellite Agementioning
confidence: 95%
“…Consequently, we test the cratering model but also infer if there may be physical processes that affect the satellite as a whole or its surface features. In this regard, Di Sisto & Zanardi (2016) analyzed the cratering process in the mid-sized saturnian satellites and calculated their surface ages. The idea is very simple and should be considered a first-order approach to the problem.…”
Section: Surface Ages or Cratering Timescalementioning
confidence: 99%
See 1 more Smart Citation
“…Multiple particle sizes from 0.6 − 15 µm are simulated for each source location, and data are generated on the impact flux in particles/sec/m 2 and mass deposition in mm/year across the surface of Enceladus. Initial simulated maps of surface deposition from the Enceladus plume published in Kempf et al (2010) have received interest from the larger research community (for example, Di Sisto and Zanardi, 2016;Nahm and Kattenhorn, 2015;Scipioni et al, 2017) and, here, we provide a more complete set of maps and data with respect to source location and particle size. Using the newly generated surface data for a curtain-style plume (Spitale et al, 2015) and the ∼ 100 discrete jets proposed in Porco et al (2014), we provide new insight into the zenith angle of plume emissions, that is, the "tilt" of the jets.…”
Section: Introductionmentioning
confidence: 99%
“…Absolute ages of geological formations on icy bodies have traditionally been estimated based on the observed crater densities for particular surface units. Different models of the impactor flux yield different age estimates, but in general these calculations indicate that the most heavily cratered icy surfaces are comparable in age to the Solar System (Zahnle et al 2003;Kirchoff and Schenk 2010;Di Sisto and Zanardi 2016;Kirchoff et al 2018). However, recent studies of the dynamical history of Saturn's satellites suggest that many of that planet's heavily-cratered mid-sized moons may be substantially less than a billion years old (Ćuk et al 2016;Asphaug and Reufer 2013).…”
mentioning
confidence: 99%